Direct Self Control-Space Vector Pulse Width Modulation Technique for Speed Control of Induction Motor using five level NPDC inverter and Sample Reference Phase Voltages - Y. Laxmi Narasimha Rao, Dr.G.Ravindranath (Drugs and Cell Therapies in Hematology, 2021)
Asynchronous motor is considered to be the best alternative for variable speed drive among ac motors due to its low cost maintenance and rugged performance. Variable speed drive of asynchronous motor is achieved by power electronic devices using V/F method which uses sinusoidal pulse width modulation and effective utilization of dc bus bar voltage is not accomplished. In this paper a new control technique for variable speed drive of asynchronous motor is achieved by using Direct Self Control-Space Vector Pulse Width Modulation Technique for Speed Control of Induction Motor using five level NPC and Sample Reference Phase Voltages. The above technique decouples flux and torque independently thereby controlling each variable separately and also space vector pulse width modulation improves the effective utilization of bus bar voltages. The above technique is simulated in Mat lab/Simulink which shows superior results when compared to conventional speed control technique.